2006
DOI: 10.1186/1749-7922-1-10
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: UARs that are performed following complicated abdominal surgeries have high mortality rates. In particular, UARs have higher mortality rates following GIS surgeries or when infectious complications occur. The possibility of efficiently lowering these high rates depends on the success of the first operations that the patient had received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 7 publications
6
29
1
1
Order By: Relevance
“…Our study showed higher mortality rate (35.3%) in those patients who had anastomotic leak as an indication for the relaparotomy. This result is also similar with other literatures [ 23 , 24 ]. Among the 12 patients who had SSI only 2 of them died post relaparotomy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our study showed higher mortality rate (35.3%) in those patients who had anastomotic leak as an indication for the relaparotomy. This result is also similar with other literatures [ 23 , 24 ]. Among the 12 patients who had SSI only 2 of them died post relaparotomy.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, patients who had anastomotic leak as an indication for the relaparotomy had a higher mortality rate (35.3%). This result is also similar with other literature [ 23 , 24 ]. Although surgical site infection rate was high, it was not significantly associated with increased mortality.…”
Section: Discussionsupporting
confidence: 94%
“…OD relaparotomy has been reported to carry higher morbidity and mortality rates among its victims. We report mortality for every 4 in 10 patients who underwent relaparotomy at MNH, a finding which is higher than that from by Unalp et al from Turkey [ 10 ]. Whether OD relaparotomy would have resulted in much lower mortality rates than what we have observed here has been ruled out [ 11 ].…”
Section: Discussionmentioning
confidence: 53%
“…Thus, it is imperative to do everything possible to minimize the chance of complications. However, in the case of fatal complications, the prompt diagnosis of complications and emergency intervention via reoperation may prevent the increased risk and even save lives [ 2 ]. Therefore, emergency reoperations following complicated surgeries are known as “final-choice operations” [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%